Enhanced biodiesel production via esterification of palm fatty acid distillate (PFAD) using rice husk ash (NiSO4)/SiO2 catalyst - Nurul Hajar, Embong; Noor, Hindryawati; Bhuyar, Prakash; Govindan, Natanamurugaraj; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (Springer Berlin Heidelberg, 2021)
Waste or low-cost feedstock utilization for preparing renewable energy is a noble effort towards a greener environment. In this work, palm fatty acid distillate (PFAD), which is usually transacted at a concession rate versus crude palm oil, is esterified to methyl esters. Conventional catalysts are not feasible in the process since PFAD consists of a significant amount of free fatty acids. As such, nickel sulfate supported on waste rice husk ash is utilized to catalyse the reaction under moderate reaction conditions of 15 wt.% catalyst, 5:1 methanol: PFAD (molar ratio) for 7 h, that produces 93% of methyl esters. The prepared catalyst was characterized for thermal stability (TGA), acid strength, surface analysis and compositional analysis via XPS, XRD and FTIR. The esterification of PFAD with NiSO4/SiO2 under the optimized reaction conditions of 15 wt.% catalyst, 5:1 methanol to PFAD molar ratio and 7 h reaction time gave the highest methyl esters conversion of 93%. The utilization of low-cost feedstock and waste utilization in catalyst preparation readily implies merits in term of environmental gains and lower cost biodiesel preparation.